Delivering the CRISPR/Cas9 system for engineering gene therapies: Recent cargo and delivery approaches for clinical translation - Foley, Ruth A.; Sims, Ruby A.; Duggan, Emily C.; Olmedo, Jessica K.; Ma, Rachel; Jonas, Steven J. (Frontiers in Bioengineering and Biotechnology, 2022)
Clustered Regularly Interspaced Short Palindromic Repeats associated protein 9 (CRISPR/Cas9) has transformed our ability to selectively edit the human genome. Requiring only a simple guide RNA, this method of targeted DNA editing has quickly become the most standardized and reproducible gene editing tool available. Catalyzing rapid advances in research, medicine, and diagnostics by increasing our understanding of gene expression, regulation, and modification, the CRISPR/Cas9 system offers the greatest potential to provide therapeutic options in the prevention and treatment of currently incurable single-gene and more complex human diseases. However, significant barriers to the clinical application of CRISPR/Cas9 remain. While in vitro, ex vivo, and in vivo gene editing has been demonstrated extensively in a laboratory setting, the translation to clinical studies is currently limited by shortfalls in the precision, scalability, and efficiency of delivering CRISPR/Cas9-associated reagents to their intended therapeutic targets. To overcome these challenges, recent advancements manipulate both the delivery cargo and vehicles used to transport CRISPR/Cas9 reagents. With the choice of cargo informing the delivery vehicle, both must be optimized for precision and efficiency. This review aims to summarize current bioengineering approaches to applying CRISPR/Cas9 gene editing tools towards the development of emerging cellular therapeutics, focusing on its two main engineerable components: the delivery vehicle and the gene editing cargo it carries. The contemporary barriers to biomedical applications are discussed within the context of key considerations to be made in the optimization of CRISPR/Cas9 for widespread clinical translation.